Education and Images in the Spectacle Society: cultural pedagogies in question - Alexandre Filordi de Carvalho (Universidade Federal do Rio Grande do Sul, 2013)
This article analyzes the reasons why the culture of images is present in the symbolic agents of the current culture, promoting educational experiences and strategies that have disseminate beyond the boundaries of formal education. The hypothesis is based on the idea that the critical analysis oriented to cultural pedagogies promotes conditions that enable the educational strategies through the use of imagetics components present in the agents of symbolic culture. To achieve this goal, it will be necessary to analyze the culture of image through the perspective of the Society of Spectacle (2000), and why the critical analysis of cultural pedagogies become essential in the educational field, challenging the actual educational practices.